Microscopical studies of necrotising scleritis. II. Collagen degradation in the scleral stroma. Issue 11 (November 1984) - Young, R. D.; Watson, P. G.
Abstract : Electron microscopy of tissue excised during surgery in eight cases of advanced anterior necrotising scleritis showed degradation of collagen in the scleral stroma by both intracellular and extracellular mechanisms. In the first of these mechanisms cells resembling active fibroblasts and macrophages were observed in the process of phagocytosis of collagen fibrils into vacuoles associated with dense cytoplasmic granules. In the second mechanism collagen fibrils in large areas of the scleral stroma appeared swollen and unravelled, or completely solubilised, without close association with stromal cells. Both activation and degeneration of stromal fibrocytes were evident in zones of extracellular fibril degradation. These changes appeared to take place prior to invasion of the stroma by cells of the granuloma.